Study on deformation difference between the contact zone and the non-contact zone of the flexible 3D stretch bending profile and roller dies based on pre-stretching amount - Liang, Jicai; Han, Chengxiang; Li, Yi; Yu, Kaifeng; Liang, Ce (International journal of advanced manufacturing technology, 2020)
Aiming at the flexible 3D stretch bending process (FSB) with multi-point die, the ABAQUS finite element software is used to simulate the bending process of the aluminum profile. In the FSB process, the deformation difference between the contact zone and non-contact zone of profile and roller dies is studied. By changing the pre-stretching amount of profile in the forming process, the finite element analysis of bending process is carried out. By measuring the height and thickness of the profile web, the influence of pre-stretching amount on the contact zone and non-contact zone is obtained. The results show that during the bending process, the points on profile deviate from the original position in height direction, which increases the web height in the non-contact zone and decrease it in the contact zone. And the points on the profile deviate from the theoretical bending position in the thickness direction of web, which leads to the web thinning in the non-contact zone and contact zone, but the thinning rules are different. When the pre-stretching amount increases, the profile web height does not change significantly in the contact zone and non-contact zone, but the thickness of profile web becomes thinner in each contact zone away from the clamp, while the thickness in the non-contact zone has no distinct change, and the thickness deformation of the web near the clamp is not obvious.